1997
DOI: 10.1007/s004150050170
|View full text |Cite
|
Sign up to set email alerts
|

High-dose intravenous immunoglobulin therapy for myasthenia gravis

Abstract: The objective of this open, retrospective study was to investigate whether intravenous immunoglobulin (IVIg) could induce a clinically obvious improvement in patients with generalized myasthenia gravis (MG), as judged by MG functional status. Fourteen patients with generalized MG were treated during at least one episode with 0.4 g IVIg per kilogram body weight per day for 5 consecutive days. Patients with confounding variables were excluded; this left 11 patients (16 episodes) to be further analysed. We define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Jongen [81] in a retrospective, unblinded and uncontrolled analysis of a small number of patients found in 56% (9 out of 16) patients improvement with the peak effect at 7 days. This was less than the 61 % of patient improvement noted by Gajdos [28].…”
Section: Intravenous Immunoglobulinmentioning
confidence: 98%
“…Jongen [81] in a retrospective, unblinded and uncontrolled analysis of a small number of patients found in 56% (9 out of 16) patients improvement with the peak effect at 7 days. This was less than the 61 % of patient improvement noted by Gajdos [28].…”
Section: Intravenous Immunoglobulinmentioning
confidence: 98%
“…Controlled clinical trials have established the efficacy of IVIg in several neuromuscular diseases, including the Guillain-Barré syndrome, chronic inflammatory demyelinating polyneuropathy, dermatomyositis and the Lambert-Eaton myasthenic syndrome [12,[15][16][17][18][19][20]. IVIg has also been demonstrated to be effective in the treatment of acute MG [21][22][23][24]. Although the mode of action of IVIg in MG is not fully understood, IVIg was shown to inhibit the binding of anti-AchR autoantibodies to AchR in vitro, by interacting with idiotypic determinants expressed by pathogenic autoantibodies [25].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, small case series have shown that IVIG also improves weakness in myasthenic crisis. [25][26][27] Thus, when patients cannot tolerate plasmapheresis because of medical comorbidities such as sepsis, severe anemia, or difficult large-bore venous access, IVIG is used as an alternative, 28 at the same dose as for GBS.…”
Section: Immunotherapymentioning
confidence: 99%